The Study of Motivation of Young Chinese Consumers toward Foreign Products - Long, Yin (2009)
The purpose of this dissertation is to find out the motivation and demands of China’s young consumers toward foreign brands and why people, especially young Chinese live in urban areas show a positive consumption to foreign products. Country of origin effect, as stated in many journals, plays an important role in consumer behaviour, which influences consumer perception of brands and purchase decisions. A structured questionnaire is designed for data collection. Factor analysis and t-test from SPSS software are used to analyse the data.